Automatic Lightweight CNN Waste Identification for Green Campus Program Support - Nouval Khairi; Yuda Apriyansyah; Haikal Habibi Siregar; Muhammad Farhan Aditya (Raskha Media Group, 2025)
Effective waste management is a key indicator of success for Green Campus Programs and a major factor in the UI GreenMetric World University Rankings. However, many Indonesian universities still face difficulties due to low accuracy in manual waste sorting, particularly for inorganic and hazardous (B3) waste. This study develops a lightweight, high-accuracy automatic waste classification system using the MobileNetV2 Convolutional Neural Network (CNN) architecture. The model was trained via transfer learning on the Kaggle “Trash Classification Dataset” (Sathish, 2023) containing 19,762 images from 10 waste classes: Metal, Glass, Biological, Paper, Plastic, Cardboard, Battery, Shoes, Clothes, and Trash. To align with operational needs of the Green Campus Program, these 10 classes were mapped into three functional categories: Organic, Recyclable, and Inorganic/B3. Experimental results show that MobileNetV2 achieved 93.2% accuracy with efficient inference time ( 4.8 ms per image) on a CPU. The prototype, built using Python Streamlit, outputs both predicted waste type and confidence percentage, making it practical for real-time campus waste sorting. The proposed model provides an intelligent, energy-efficient, and transparent solution to support sustainable waste management, addressing key operational challenges in inorganic (WS4) and hazardous (B3) waste (WS5) handling